Otoacoustic Emissions in Sudden Sensorineural Hearing Loss: Changes of Measures with Treatment - Shadman Nemati; Seyyed-Ebrahim Naghavi; Ehsan Kazemnejad; Roozbeh Banan (Iranian Journal of Otorhinolaryngology, 2011)
Introduction: To identify changes in OAEs parameters in treatment course of idiopathic sudden sensorineural hearing loss (iSSNHL). Materials and Methods: In aprospective studyfromAugust 2005 to January 2009, 26 patients with iSSNHL underwent conventional audiometry/tympanometry and two types of OAEs (TEOAEs and DPOAEs) before and after the completion of standard drug therapy.The changes in pre- and post- treatment parameters were compared with each other and with normal-contralateral ears. Results: In TEOAEs, the mean overall correlation (reproducibility) and the mean overall strength in involved ears were 10.96±23.36 and 0.99±3.45 dB, respectively, before the treatment, which reached 22.88±36.55 and 1.85±5.3, respectively, after the treatment (P>0.05). Significant difference between “correlation score” (average of correlations at 3-4 involved frequencies) before and after treatment was found: 6.52 ±18.19 vs. 21.67±37.8 (P